Explorasi Hubungan Self-Compassion dan Kecemasan: Analisis Bibliometrik Satu dekade terakhir - Alim, Muhamad Ardhi (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the relationship between self-compassion and anxiety using a bibliometric approach over the last decade (2014–2024). Self-compassion, which consists of elements of kindness toward oneself, awareness of universal human experiences, and nonjudgmental attention to emotions, has been identified as an important factor in managing anxiety. This analysis uses bibliometric methods based on Biblioshiny software in R to analyze 133 relevant articles from various databases. The results show a significant increase in the number of related publications, with the journal Frontiers in Psychology and Mindfulness being the main source. Keywords such as mindfulness, resilience, and mental health often appear alongside self-compassion, highlighting the important role this concept plays in strengthening emotional resilience and reducing anxiety. This research contributes to the development of positive psychology-based interventions that can improve mental well-being, as well as providing insight for practitioners in designing more holistic and effective mental health strategies.